ANALISIS PENGARUH KUALITAS PRODUK, KUALITAS LAYANAN, PROMOSI, HARGA DAN PENGGUNAAN QRIS (QUICK RESPONSE CODE INDONESIAN STANDARD) TERHADAP KEPUTUSAN PEMBELIAN MAHASISWA PADA COFFEE SHOP EMBUN SENJA - Azka, Muhammad Irfan; Tri Astuti, Sri Rahayu (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT Embun Senja is one of the coffee shops in the city of Semarang which can attract as many as 500-1,000 consumers a day. Initially, the market segmentation focused on the general public, but as the market developed, the market segmentation was students, even though the price offered was relatively expensive compared to other competitors. This study aims to analyze the effect of product quality, service quality, promotional prices, and the use of QRIS on students' purchasing decisions at Coffee Shop Embun Senja, Semarang. This research is classified as a quantitative analysis with primary data obtained through the results of the respondent's questionnaire. The population in this study were all students in the city of Semarang, while the sample for this study was set at 100 respondents. The method used to identify the effect of the independent variables on the dependent variable is multiple linear regression. The results showed that the variable product quality, service quality, promotion, and price had a significant positive effect while the use of QRIS had no significant effect on purchasing decisions. The use of QRIS does not have a significant impact on purchasing decisions because the majority of Coffee Shops in the Tembalang and Banyumanik areas (competitors) already use QRIS as non-cash payment transactions so that in this case it provides a perception of convenience but has a significant impact on purchasing decisions. Statistical tests show that promotion is the factor that most influences purchasing decisions followed by price, product quality, use of QRIS, and service quality.